فقه المرأة في النوازل الطبية - جيجان, قيس ناظم (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The research titled "Women's Jurisprudence in Medical Innovations" explores the Islamic legal rulings on emerging medical issues specific to women, such as artificial insemination, organ transplantation, stem cell therapy, cosmetic surgeries, and abortion. The study aims to clarify the Islamic stance on these matters while highlighting the flexibility of Islamic law in adapting to modern medical advancements. It employs the inductive method to gather religious texts, the analytical method to derive rulings, and the comparative method to analyze the opinions of seven Islamic schools of thought. The research emphasizes women's medical rights, confidentiality of health information, and the balance between science and Islamic law. The study concludes that Islamic jurisprudence effectively addresses scientific advancements while safeguarding women's dignity and ensuring justice.